Internalizing The Values of Bhinneka Tunggal Ika among The Mediatized Young Generation Ahead of The 2024 Elections - Ririt Yuniar; Meydisah Olivia (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
Internalizing the values of Bhinneka Tunggal Ika is crucial to explore further, especially in the context of Indonesia's diverse society. Various perspectives of young people in considering the 2024 presidential candidates in Indonesia have the potential to cause division. This article addresses three key points: firstly, the importance of internalizing the values of Bhinneka Tunggal Ika in creating a peaceful elections atmosphere; secondly, factors influencing the young generation’s responses to the 2024 elections; thirdly, implications of implementing the values of Bhinneka Tunggal Ika on the behavior of young voters in the 2024 elections. Using a mixed method approach, with data collected through surveys and analyzed qualitatively, this study revealed three key points. First, internalizing the values of Bhinneka Tunggal Ika is essential to foster peaceful elections in 2024. Second, socializing the implementation of the values of Bhinneka Tunggal Ika is one of factors that could influence the behavior of young voters in creating peaceful elections in 2024. Third, the internalization of these values could lead the young generation to adopt more inclusive and tolerant perspective on political issues. However, the complexity produced by mediatization do not fully reflect the high awareness of the values of Bhinneka Tunggal Ika. Best practices for the young generation are expected to be able to implement the values of Bhinneka Tunggal Ika consistently in social life and the democratic process, including tolerance for differences of opinion, diversity, and harmony in various perspectives